M.G. STATE SCIENTIFIC SCHOOL - Yashin kizi, Nishanova Zulfizar (Confrencea, 2023)
M.G. Davletshin, doctor of psychology, professor, honored scientist of Uzbekistan, is a great scientist who made a great contribution to the development of science in the Republic and was able to create a unique scientific school. Two directions can be distinguished in the historical development of "M.G. Davletshin Scientific School":